O uso da língua materna nas aulas de língua estrangeira: estado de arte e propostas - MANESCHY, Vanessa Bezerra (2007)
This work intends to analyze the use of mother tongue in the foreign language classroom. In order to do this, firstly, we will point out the moments in which the mother tongue is considered according to many language learning methodologies, also, causes of its exclusion and reasons to include the mother tongue will be mentioned so that finally, we can propose a categorization that presents functions of the mother tongue in the foreign language learning context. A field research involving three English learning institutions in the state of Pará was done in order to observe if the mother tongue is in fact present in this context, and if so, in what frequency is it done; which functions does it perform; which functions are dominant, so that we can evaluate if the use of mother tongue favors or not foreign language learning.